1999
DOI: 10.1103/physrevb.59.7108
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional arrays of Josephson junctions in a magnetic field: A stability analysis of synchronized states

Abstract: We report the results of a Floquet analysis of two-dimensional arrays of resistively and capacitively shunted Josephson junctions in an external transverse magnetic field. The Floquet analysis indicates stable phase locking of the active junctions over a finite range of values of the bias current and junction capacitance, even in the absence of an external load. This stable phase locking is robust against critical current disorder, up to at least a Ϯ25% rms spread in critical currents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Furthermore, such locking survives weak disorder in the critical currents. The effectiveness of a magnetic field in producing phase locking in square arrays has been discussed previously [21,22]. The present work provides additional evidence that a field f = 1/2 is effective in producing phase locking, even when the applied current has nonzero components parallel to both array axes [23].…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, such locking survives weak disorder in the critical currents. The effectiveness of a magnetic field in producing phase locking in square arrays has been discussed previously [21,22]. The present work provides additional evidence that a field f = 1/2 is effective in producing phase locking, even when the applied current has nonzero components parallel to both array axes [23].…”
Section: Discussionmentioning
confidence: 56%
“…It was shown in Ref. [37] that underdamped arrays in an external magnetic field perpendicular to the plane of the array could lift this degeneracy via the coupling of the junctions to the external magnetic field in the gauge-invariant phase difference. In the presence of critical current disorder, however, numerical simulations of the RSJ equations revealed that frequency synchronization was no longer possible.…”
Section: "Small-world" Connections In Two-dimensional Arraysmentioning
confidence: 99%
“…The relation between Cellular Neural Network (CNN) and the Josephson Transmission Line (JTL) array has been studied in many publications see for example [1], [5]. Two-dimensional array of Josephson Junctions is considered in [1].…”
Section: Cellular Neural Network Computing Of the Interaction Of Fluxonsmentioning
confidence: 99%
“…For this reason, fluxons have applications in information processing of electronic devices. In fact fluxons arise in the well known Josephson Junction (JJ) which is used in many applications in superconductor electronics [5].Recently, JJ have been considered as a source of THz radiation. Fluxons moving coherently in such junctions are a possible source of radiation.…”
Section: Introductionmentioning
confidence: 99%